2015
DOI: 10.1007/s13277-015-3706-6
|View full text |Cite
|
Sign up to set email alerts
|

Folate-conjugated nanoparticles as a potent therapeutic approach in targeted cancer therapy

Abstract: The selective and efficient drug delivery to tumor cells can remarkably improve different cancer therapeutic approaches. There are several nanoparticles (NPs) which can act as a potent drug carrier for cancer therapy. However, the specific drug delivery to cancer cells is an important issue which should be considered before designing new NPs for in vivo application. It has been shown that cancer cells over-express folate receptor (FR) in order to improve their growth. As normal cells express a significantly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 164 publications
(184 reference statements)
0
53
0
1
Order By: Relevance
“…We utilized folic acid (FA) conjugation on the AuNP-sushi conjugates to enhance their internalization and further improve their antibacterial activity. The overexpressed folate receptors (FR) on cancer cells increases the internalization of NPs containing FA via receptor mediated endocytosis 42–44 . Many studies have shown that modifying NPs with FA ligands improves targeting and uptake of drugs by cancer cells which has a huge potential for selective delivery of chemotherapeutic agents to FR-positive cancer cells 27, 4446 .…”
Section: Discussionmentioning
confidence: 99%
“…We utilized folic acid (FA) conjugation on the AuNP-sushi conjugates to enhance their internalization and further improve their antibacterial activity. The overexpressed folate receptors (FR) on cancer cells increases the internalization of NPs containing FA via receptor mediated endocytosis 42–44 . Many studies have shown that modifying NPs with FA ligands improves targeting and uptake of drugs by cancer cells which has a huge potential for selective delivery of chemotherapeutic agents to FR-positive cancer cells 27, 4446 .…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this, a ligand is used for active targeting of drug delivery. Folic acid, an attractive ligand to folate receptors, is known to be a potential targeting substance to deliver the therapeutic agents through receptor-mediated endocytosis because of the overexpression of folate receptors in the number of human cancer cells that serve as a symbol of tumour, and provide a distinguishable marker from normal cells 31,32 . The effective delivery of drugs to the target site can be attained through biological interactions like antigen-antibody binding called targeted drug delivery.…”
Section: Chitosan-folic Acid Conjugation and Active Targetingmentioning
confidence: 99%
“…Selection of suitable natural polymers for development of nanoparticles provides additional benefits of enhanced stability, biocompatibility, biodegradability, nonimmunogenicity and non-toxicity. New generation of nanoparticles can be developed with newer natural polymers with remarkable biopharmaceutical properties such as health-promoting effects, inherent pharmacological activities, haemocompatibility, responsiveness to specific internal stimuli and tunable chemical properties (Bahrami et al, 2015;Fernández Diaz et al, 2017). Quantum dots are specialised nanocrystals or nanofactories used as fluorescent markers for live cellular imaging, especially in cancer therapeutics because of their superior size control effect through compartmentalization in the periplasmic space and vesicles.…”
Section: Introductionmentioning
confidence: 99%